Estructuración e implementación de un modelo para la integración al sistema gestión de calidad, de la gestión ambiental y de seguridad, en la Empresa Eléctrica Quito - Herrera, Marco Vinicio (2014)
The global trend in the organizational environment is to integrate management systems to ensure users , products and quality services that meet customer requirements and legal , ensuring minimal effect on the environment and care for the person personnel , safety and health at work. Based on this expectation, organizational leaders are training and training their middle and senior management in integrated management systems for quality, environment and safety , finding strategic partners in university and polytechnic schools , fourth level programs that are aligned strategic planning of the State, in the case of Ecuador , it is called National Plan for Good Living . This work aims to develop a model to integrate the System Management Utility Quality Quito , environmental management , management of health and safety at work which, at present, is managed independently . Model that can be replicated or adopted by other companies distributing electricity in the country , considering that the Ministry of Electricity and Renewable Energy, has a policy to standardize the management systems of the electricity distribution sector . To show that it is possible to integrate the system of quality management , environmental management and management of health and safety at work, in the different chapters of the thesis , it is evident that there are common elements to be aligned so that they can manage and control centrally, in compliance with the existing legal framework .